PEMANFAATAN KULIT UBI KAYU FERMENTASI DENGAN METODE TAKAKURA DALAM PAKAN TERHADAP PERTUMBUHAN KELINCI NEW ZEALAND WHITE JANTAN LEPAS SAPIH - edi gurusinga (Universitas Sumatera Utara, 2013)
Fermented cassava peel with takakura methode can increase the protein content of feed implications for improving the quality of feed. This study aims to determine the effect offermented cassava peel fermented with takakura methode in feed on the growth of New Zealand white rabbit offa weaning. The experiment was conducted in the Laboratory of Animal Biology, Faculty of Agriculture, University of North Sumatera, Medan. Research carried out for 2 months starting from September to November 2012. The research design was used in this study was completely randomized design (CRD) with 4 treatments. Treatment consists of P0 (0% fermented cassava peel), P1 (10% fermented cassava peel), P2 (20% fermented cassava peel) and P3 (30% fermented cassava peel). The results showed that administration of a variety of fermented cassava peel levels of takakura method were significantly different (P <0.01) for decreasing of consumption, decreasing of body weight gainnand increasing of convertion. Keywords: cassava peel, fermented, takakura method, rabbit